2003
DOI: 10.1046/j.1523-1755.2003.00272.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between duration of brain death and hemodynamic (in)stability on progressive dysfunction and increased immunologic activation of donor kidneys

Abstract: Brain death causes progressive kidney dysfunction. Also, inflammatory responses reflecting tissue injury are caused by brain death. When hemodynamic instability in the brain-dead donor is not corrected, kidney dysfunction is enhanced and immune activation occurs faster and is more profound. The observed changes may predispose the graft for additional ischemia/reperfusion injury during the transplant process and hence accelerate rejection of the graft after transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
84
1
5

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 129 publications
(98 citation statements)
references
References 29 publications
8
84
1
5
Order By: Relevance
“…In another study on kidney histology, van der Hoven et al 13 found similar results to those observed previously on liver,…”
supporting
confidence: 78%
“…In another study on kidney histology, van der Hoven et al 13 found similar results to those observed previously on liver,…”
supporting
confidence: 78%
“…Donor optimization resulted in better kidney and liver function, but did not inhibit the inflammatory and immunological response in the liver, which increased progressively with time (26). In a similar study from the same group, maintaining donor normotension was found to delay progression of immunological activation in the kidneys (44). The authors suggested that the inflammatory response after brain death is a progressive phenomenon and that time to organ procurement should be kept as short as possible.…”
Section: Discussionmentioning
confidence: 85%
“…Sham-operated rats remained ventilated and anesthetized for half an hour, and then sacrificed. In previous studies, additional controls have been considered; sham animals kept under anesthesia for 4-6 h or hemodynamically unstable non brain-dead animals had only minimal upregulation of pro-inflammatory markers (18).…”
Section: Animals and Experimental Protocolsmentioning
confidence: 99%